Banking reforms, performance and risk in China. Issue 40 (27th August 2017) - He, Liangliang; Chen, Lei; Liu, Frank Hong
ABSTRACT: We investigate the impact of the banking reform started from 2005 on ownership structures in China on commercial banks' profitability, efficiency and risk over the period 2000–2012, providing comprehensive evidence on the impact of banking reform in China. We find that banks on average tend to have higher profitability, lower risk and lower efficiency after the reforms, and the results are robust with our difference-in-difference approach. Our results also show that the Big 5 state-owned banks (SOCB) underperform banks with other types of ownership when risk is measured by non-performing loans (NPLs) over the entire study period but tend to have fewer NPLs than other banks during the post-reform period. Our results provide some supporting evidence on the ongoing banking reforms in China, suggesting that attracting strategic foreign investors and listing SOCBs on stock exchanges appear to be effective ways to help SOCBs deal with the problem of NPLs and manage their risk.